Evaluation of bearing capacity of PHC pipe piles via the dynamic and static loading test - Li, Caihua; Li, Xuepeng (Frontiers in Earth Science, 2023)
Static load test (SLT) is commonly used to validate the design of PHC pipe piles and as a proof test for production piles. However, the High Strain Dynamic Test (HSDT) offers an alternative approach to SLT for estimating the bearing capacity of piles due to its faster implementation and potential cost savings. In order to provide the error sources of bearing capacity and to determine the design parameters of pile foundation engineering for HSDT in a reasonable manner. This report presents a study of bearing capacity study via the HSDT and SLT with a sliding micrometer. This study employs a Pile Driving Analyzer (PDA) imported from the United States. In addition, sliding micrometers with cone-shaped rings are placed every 1 m are embedded in the inner side of the pile piles for measuring the strain. In this paper, the law of stress and strain at various depths during loading is presented. A new concept of “inflection point” is proposed between shaft resistance and relative displacement of pile-soil. Furthermore, the relationship between toe resistance and settlement of pile is demonstrated by comparing the SLT and HSDT. Finally, the error of bearing capacity between SLT and HSDT with CAPWAP studies revealed that the HSDT could provide adequate findings for assessing the bearing capacity of PHC pipe piles.